2016
DOI: 10.7196/samj.2016.v106i5.9949
|View full text |Cite
|
Sign up to set email alerts
|

Identity tags: A vector for cross-infection?

Abstract: Prevention of hospital-acquired infections is important in any setting. The ID tag has been identified as a possible source of infection spread in this and previous studies. The ID tag has to date been neglected as a potential source of pathogen spread, and efforts to make staff aware of this potential danger should be considered in every institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In line with the current work, Cox et al (7) showed that decontamination practices by 52% of staff were more prevalent than in previous reports (16% and 27%) (20,21) . The tags that had never been cleaned were more likely to carry pathogenic growth.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with the current work, Cox et al (7) showed that decontamination practices by 52% of staff were more prevalent than in previous reports (16% and 27%) (20,21) . The tags that had never been cleaned were more likely to carry pathogenic growth.…”
Section: Discussionsupporting
confidence: 90%
“…At Red Cross War Memorial Children's Hospital (RCWMCH), Cape Town, South Africa, as at many other institutions worldwide, these access and ID tags are worn around the neck on a lanyard (7) . Mobile phones have become one of the most indispensable accessories of both social and professional life.…”
Section: Introductionmentioning
confidence: 99%
“…Displaying ID badges are essential for healthcare as they serve as a secondary form of identification used to access controlled areas. Several studies have shown that cleaning or disinfecting ID badges is associated with the incidence of pathogen colonization [22,23]. The relevance of neckties and ID badges as a part of formal physician attire warrants further investigation as they have the potential to serve as a vector for nosocomial pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…HAIs, particularly the ones involving resistant microorganisms, lead to difficult complications in contemporary medicine [45]. Antibiotic resistant strains represent serious healthcare complications [46,47].…”
Section: Nosocomial Pathogens Resistant To Methicillinmentioning
confidence: 99%